Basic Principles and Basic Rules of Islamic Law - Hasan Munthe; Febrianti Lingga (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
Islamic law is a legal system that originates from revelation and has unique characteristics. This research aims to examine the basic principles and rules of Islamic law as a basis for determining law. The method used is qualitative research with a normative approach through literature review. The research results show that the basic principles of Islamic law include justice (al-'adl), benefit (al-maslahah), legal certainty, and flexibility. The principles of Islamic jurisprudence, such as al-umūr bi maqāṣidihā, al-ḍarar yuzāl, and al-mashaqqah tajlib al-taysīr, serve as a methodological framework in establishing law. Thus, these principles and rules are important in legal istinbāṭ so that it remains relevant and responsive to developments in society.